2017
DOI: 10.1097/pcc.0000000000001059
|View full text |Cite
|
Sign up to set email alerts
|

Finding Diagnostic Errors in Children Admitted to the PICU

Abstract: The Safer Dx Instrument has high reliability and validity for diagnostic error detection when used in high-risk pediatric care settings. With further validation in additional clinical settings, it could be useful to enhance learning and feedback about diagnostic safety in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
0
34
2
Order By: Relevance
“…Studies have shown that diagnostic errors and incorrect evaluations by physicians and health practitioners can range from 12% to 35%. 25,26 In addition, multiple studies have observed intra- and interobserver clinical assessment correlations between physicians and specialty trained health professionals to range between 22% and 73%. 2729 Such variability between health-care professionals also likely contributed to our inter-rater reliability kappa value analysis (Table 4), thus supporting the Gwet’s AC 1 approach as a more reliable inter-rater reliability analysis for this study design.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that diagnostic errors and incorrect evaluations by physicians and health practitioners can range from 12% to 35%. 25,26 In addition, multiple studies have observed intra- and interobserver clinical assessment correlations between physicians and specialty trained health professionals to range between 22% and 73%. 2729 Such variability between health-care professionals also likely contributed to our inter-rater reliability kappa value analysis (Table 4), thus supporting the Gwet’s AC 1 approach as a more reliable inter-rater reliability analysis for this study design.…”
Section: Discussionmentioning
confidence: 99%
“…There is also an opportunity to leverage peer review programs to improve diagnostic self-assessment, feedback, and improvement [42]. Similarly, autopsy reports [43], diagnostic discrepancies at admission versus discharge [44,45], escalations of care [46,47], and malpractice claims [48][49][50][51] may be reviewed with special attention to opportunities to improve diagnosis. These data sources may not shed light on the frequency or scope of a problem, but they can help raise awareness of the impact and harm of diagnostic errors and, in some cases, specific opportunities for improvement.…”
Section: Learning From Known Incidents and Reportsmentioning
confidence: 99%
“…1 There is now a solid—and growing—body of evidence showing that diagnostic errors occur with substantial frequency in inpatients, outpatients, and even children. 24 The causative factors contributing to diagnostic errors are both complex and increasingly understood across multiple contexts. Cognitive factors— related to both lack of and misapplication of knowledge as well as faulty cognition—contribute substantially to diagnostic errors as do factors related to the flawed “nonsystem” that is the US health care system.…”
mentioning
confidence: 99%